1988
DOI: 10.2118/16951-pa
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomography for Rock-Property Determination and Fluid-Flow Visualization

Abstract: This paper discusses the development and application of X-ray computed tomography (CT) for the determination of rock properties and the study of miscible displacements in laboratory cores. Saturation (relative permeability) and porosity measurements by CT scanning are described, and the results are compared to those of conventional methods. Results of corefloods with miscible fluids show the influence of rock heterogeneities (bedding planes) and mobility ratio on volumetric sweepout. The corefloods also illust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
86
0
11

Year Published

1997
1997
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(97 citation statements)
references
References 12 publications
0
86
0
11
Order By: Relevance
“…Withjack (1988) has shown that porosity can be calculated from the matrix of CT numbers obtained -38 - …”
Section: Water Imbibition Into a Dry Fractured Corementioning
confidence: 99%
“…Withjack (1988) has shown that porosity can be calculated from the matrix of CT numbers obtained -38 - …”
Section: Water Imbibition Into a Dry Fractured Corementioning
confidence: 99%
“…Then oil was injected into the core until 100% saturated with oil and a second set of images acquired. The voxel-by-voxel values of porosity were calculated (Withjack, 1988) as,…”
Section: Methodsmentioning
confidence: 99%
“…El principal campo de aplicación de la Tomografía Computarizada ha sido el diagnóstico médico, aunque también ha sido usada extensivamente en la industria de hidrocarburos para el estudio de muestras de roca de yacimientos de petróleo por cerca de 20 años (Bansal e Islam, 1991;Hunt et al, 1998;Kantzas, 1990;Wellington y Vinegar, 1987;Withjack, 1988). Las aplicaciones de la Tomografía Computarizada en la industria de hidrocarburos se concentran principalmente en el escaneo de medios porosos sin comprometer su integridad física ni humectabilidad.…”
Section: Tomografía Computarizada De Rocasunclassified
“…Esta requiere el uso de trazadores radiopacos (dopantes) para monitorear el movimiento de fluidos dentro de una muestra de roca. Los dopantes proveen suficiente información del contraste entre las diferentes fases líquidas al interior de la muestra de roca, y permiten cuantificar la distribución de saturación de fluidos al interior de la misma (Withjack, 1988).…”
Section: Tomografía Computarizada De Rocasunclassified